2019
DOI: 10.9744/ijbs.2.2.96-108
|View full text |Cite
|
Sign up to set email alerts
|

Do Value Added Intellectual Coefficient and Corporate Governance Contribute to Firm's Economic Value Added

Abstract: This study is about examining the influence of Intellectual Capital and Corporate Governance to EVA. Data used in this study were collected from a sample of 121 consumer goods companies in Indonesia and Malaysia from 2010 to 2017. Panel data multiple regression was performed to examine the research framework. The intellectual capital was measured by VAIC value, while the corporate governance was explained by the audit committee, remuneration board, and auditor quality and tenure. This study found that HCE, SCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Ha5 is rejected, which means that audit quality as proxied by KAP size (Big Four and non-Big Four) does not have a positive effect on shareholder value creation as proxied by EVA. This is different from the research results of Hatane et al [21] which showed that audit quality had a significant positive effect on EVA. The data shows that the observations audited by the Big Four KAPs on average have a higher WACC, with an average of 9.47%, compared to observations audited by non-Big Four KAPs with an average WACC of 8.24 %.…”
Section: Table 2 Results Of Statistical Test-tcontrasting
confidence: 99%
See 2 more Smart Citations
“…Ha5 is rejected, which means that audit quality as proxied by KAP size (Big Four and non-Big Four) does not have a positive effect on shareholder value creation as proxied by EVA. This is different from the research results of Hatane et al [21] which showed that audit quality had a significant positive effect on EVA. The data shows that the observations audited by the Big Four KAPs on average have a higher WACC, with an average of 9.47%, compared to observations audited by non-Big Four KAPs with an average WACC of 8.24 %.…”
Section: Table 2 Results Of Statistical Test-tcontrasting
confidence: 99%
“…A causal study is a research study conducted to prove a cause and effect relationship between variables [22]. The following are the measurements of the variables in this study: [4] Board size = jumlah anggota dewan direksi [23] CIND = Jumlah dewan komisaris independen Jumlah total anggota dewan komisaris [24] FCF = Cash flows from operating activities -Cash used to purchase PP&E [7] Audit quality = Dummy 1 for Big 4, 0 for non-Big 4 [21] The data used in this research is secondary data. In this study, the sample was selected using purposive sampling method.…”
Section: Methodology and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a cue from Hatane et al (2019), Bassetti et al (2019) and Sunariyanto (2020), the VAIC model is used to examine the effects of Intellectual Capital on the financial performance in the SADC general insurance sector for 2008 to 2019. The year 2008 was chosen because Africa's insurance sector has been besieged since the 2008 Global Financial Crisis.…”
Section: Methodsmentioning
confidence: 99%